Chemometric analysis of UV-spectra: a novel, rapid and cheap method to differentiate bovine, porcine and fish gelatin - Hammed, Ademola Monsur; Tawakalit Tope, Asiyanbi-Hammed; Low, Kan Hin; Idris Oseni, Munirat Abolore (2017)
We have developed a novel, fast and cheap methods that use UV-spectroscopy to differentiate gelatin based on source. Fish gelatin can be differentiated from mammalian gelatin in the PCA component 1, while PCA component 2 was able to differentiate the mammalian gelatin when compared together. Chymotrypsin hydrolysis of gelatin prior to analysis improved the discriminating efficiency of the developed method. Future works will focus understanding the reaction mechanisms.